If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(7x + 9) = 49x + -10 Reorder the terms: 7(9 + 7x) = 49x + -10 (9 * 7 + 7x * 7) = 49x + -10 (63 + 49x) = 49x + -10 Reorder the terms: 63 + 49x = -10 + 49x Add '-49x' to each side of the equation. 63 + 49x + -49x = -10 + 49x + -49x Combine like terms: 49x + -49x = 0 63 + 0 = -10 + 49x + -49x 63 = -10 + 49x + -49x Combine like terms: 49x + -49x = 0 63 = -10 + 0 63 = -10 Solving 63 = -10 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -6x+6x+14=14 | | 9m-14= | | x*.10=x*.15 | | 14-3n=26 | | 8c+5(c-3)= | | x^3-3x^2+9x-27=0 | | 5x-30=40+3x | | 2x+7=2x-4 | | 8c+(5c-3)= | | 5b+4=2(b+2) | | 9k-19-8k=-2k+11 | | 143+2x=-10x+1 | | 12y+2(13y+4)=122 | | v+7=3v-3 | | 0.67+0.13t=2.49t-1.10 | | 2m-1+4m=-13 | | -13=5-13+3a | | 25s^4-9p^2=0 | | 5x-3(x-3)=-6-4x+7 | | 7n=2n-36 | | s=2*3.14r*r | | 7(13x+9)+17x=-8x+18 | | 8(w+17)= | | 4=2.5g | | 5n-12=35 | | 1200x+250=3500 | | -5b+3=-72 | | q^2+6q+9-p^2=0 | | 7(13x+9)+17x=-8+18 | | 3.7x+47.4=16.4-11.8x | | 9g-10-14g=-3g+14 | | .5d-4=1 |